The Effect Of Giving Maggot (Chrysomya megacephala) Maintained In Different Media On The Production Performance Of Nile Fish (Orechromis niloticus) - Imam, Imam Agus Faisal; Scabra, Andre Rachmat; Asri, Yuliana (Jurnal Media Akuakultur Indonesia, 2025)
Nile tilapia is a high-value aquaculture commodity. Its production increased from 24.98% in 2018 to 26.76% in 2019, showing a 7.11% rise. In tilapia farming, feed is a major factor, but its high cost has encouraged the search for alternative feeds. Maggot offers a promising solution due to its low cost and high protein content (40–50%) along with essential amino acids. This research used an experimental method with a completely randomized design (CRD), consisting of 4 treatments and 3 replications: P1 (household waste), P2 (fruit waste), P3 (tofu dregs), and P4 (chicken manure). Egg hatching was carried out in plastic containers with a moist mixture of pellet and water. After one week, larvae were transferred to wooden rearing containers filled with 2 kg of each type of waste. The maggot rearing process lasted for two weeks. Maggots were harvested at three weeks old, then dried by roasting and used as fish feed. Tilapia were reared for 45 days in 12 aerated containers and fed maggots three times a day. Water quality was monitored weekly. The results showed that weight gain, specific growth rate (SGR), absolute length, specific length growth rate (SLGR), and blood glucose levels were significantly affected by the treatments. However, feed conversion ratio (FCR) and survival rate (SR) were not significantly different. The best results were obtained from P1 (household waste), with absolute weight gain of 11.42 g, SGR of 1.67%/day, absolute length of 4.92 cm, SLGR of 1.02%/day, FCR of 1.9, survival rate of 84.44%, and blood glucose level of 73.3 mg/dL.